Multidisciplinary Approach for Retinoblastoma Management - Thakur, Sristi; Basnet, Rakshya; Bajracharya, Kabindra (Nepalese Journal of Ophthalmology, 2021)
We read with keen interest the article by Shah et al "Pathologic Risk Factor in Retinoblastoma: An Institutional Experience Based on Analysis of Enucleated Eyes"(Shah A et al, 2012). They have highlighted high-risk histopathological features in Retinoblastoma with retrolaminar optic nerve invasion being the most common and also showed statistically significant correlation of high risk histological features with tumor size and AJCC stage of tumor. Their aim to assess the frequency and spectrum of high risk histopathological features in enucleated specimens of retinoblastoma was successful which may guide the clinician in timely planning for subsequent neoadjuvant therapy and prevent further ocular morbidity and mortality in children. We would like to congratulate authors for this article and with invoked interest it led us to go in more depth and we wish to discuss several aspects of the study that can potentially influence the results.